Perilaku Penggunaan Pestisida Berhubungan dengan Keluhan Kesehatan Petani Padi - Risma Widianingsih; Ratna Muliawati; Mushidah Mushidah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
The use of pesticides that are not in accordance with the rules can cause health complaints to farmers. This study aims to analyze the behavior of pesticide use on health complaints on rice farmers in the Village Kebonsari District Rowosari Kendal. This research is an observational analytic research with cross sectional approach (cross section). The population in this study amounted to 277 farmers with a total sample of 67 respondents. Samples were taken by purposive sampling technique from all farmer population of pesticide user in KebonsariVillag. Data were collected through observation and questionnaires.The results obtained were analyzed using Fisher Exact Test. The results showed that there was a significant correlation between pesticide use behavior with health complaints felt by farmers(p value = 0.000.